Computational searching for new stable graphyne structures and their electronic properties. (March 2016) - Kim, Hahn; Kim, Yeonjoon; Kim, Jaewook; Kim, Woo Youn
Abstract: We devised a useful computational strategy to search for new types of stable two-dimensional carbon allotropes. As an illustration, we considered all the isomers of C18 H6 and found three stable building units for graphynes. Then, we investigated the stability of each unit {hexagonal/triangular/parallelogrammatic C18 H6 (C18 H6 h /C18 H6 t /C18 H6 p )} in that π-conjugation effects improve the stability and conductivity of the system. The resonance energies of the above C18 H6 are smaller than that of benzene, but still large; among the three types, C18 H6 t is the most stable, followed by C18 H6 p . This supports why the graphyne composed of C18 H6 t was already synthesized, while it is likely that the graphynes composed of C18 H6 h and C18 H6 p could also be synthesized. The graphynes composed of C18 H6 h and C18 H6 p were predicted to have zero band gaps with Dirac cones, whereas that composed of C18 H6 t turned out to be a semiconductor with the band gap of 0.49 eV. In particular, C18 H6 p has not only direction-dependent Dirac cones but also their unconventional locations in the first Brillouin zone.